Development of Antibacterial Polyester Fabric by Growth of ZnO Nanorods. Issue 1 (March 2014) - Ashraf, Munir; Dumont, Frédéric; Campagne, Christine; Champagne, Philippe; Perwuelz, Anne; Leriche, Anne; Chihib, Nour-Eddine
ZnO nanorods were grown on polyester fabric by hydrothermal process. The seeding of fabric to grow ZnO nanorods was necessary because they did not grow without seeding. An air plasma treatment was carried out on polyester fabric to generate polar groups which could attach ZnO seeds. ZnO nanorods were grown on these seeds. The generation of polar groups was confirmed by XPS analysis. The morphology of nanorods was characterized with SEM and TEM. The quantity of ZnO deposited on fabric in the form of nanorods was estimated to be 5.6 % w/w by atomic absorption spectroscopy. Two Gram negative bacteria; Escherichia coli and Pseudomonas aeruginosa and a Gram positive; Staphyloccocus aureus were used for antibacterial activity evaluation by qualitative method. E. coli and S. aureus were used for quantitative assessment by using NF ISO 20743:2009 Transfer Method. It was noted that the functionalized fabric prevented the growth of bacteria not only on and below the fabric but also in the immediate proximities for all three bacteria. It was also observed that the fabric was more effective against Gram positive as compared to Gram negative bacteria. Moreover, it was shown that UV pre-activation of functionalized fabric enhanced the antibacterial activity.